Advances in closed (recirculated) system mariculture - Price, Kent S. (Revista de Biología Tropical, 2024)
Man has practiced various forms of aquaculture for thousands of years. Most of his efforts have been directed toward manipulation of natural systems. However, experience in agriculture, which has had the technological advantage of several hundreds of years of developmental effort, has shown that certain crops (poultry, winter tomatoes, mushrooms, flowers, etc.) are best produced in artificial or otherwise highly controlled environments. It has become apparent to us at Delaware that such may be the case with bivalve filter-feeding shellfish.